Living in the Internet of Things: Cybersecurity of the IoT - 2018 2018
DOI: 10.1049/cp.2018.0019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cyber Risk and Associated Concentration of Research (ACR)2 in the Security of Vehicular Edge Clouds

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRAP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Replay attacks can be used to manipulate the vehicle locations by re-transmitting the previous messages [79]. The adversary can target LiDAR [80], CAN bus [50], keyless entry systems [54], authorization and key agreement protocols [52], or communication between CAVs and RSU [26] in EC-CAVs that can further lead to unauthorized data transmission, Eavesdropping, or Sniffing.…”
Section: Defenses Against Replay Attackmentioning
confidence: 99%
See 3 more Smart Citations
“…Replay attacks can be used to manipulate the vehicle locations by re-transmitting the previous messages [79]. The adversary can target LiDAR [80], CAN bus [50], keyless entry systems [54], authorization and key agreement protocols [52], or communication between CAVs and RSU [26] in EC-CAVs that can further lead to unauthorized data transmission, Eavesdropping, or Sniffing.…”
Section: Defenses Against Replay Attackmentioning
confidence: 99%
“…Lu et al [79] reported that timing attacks in Intelligent Transportation Systems (ITS) can delay the transmission of security messages, which can lead to accidents. [90] Packet leashes mechanism.…”
Section: Defenses Against Timing Attackmentioning
confidence: 99%
See 2 more Smart Citations
“…A legitimate vehicle believes that it has received a message from another legitimate vehicle even though it was sent by attackers. The real identity of the attackers cannot be detected [57]. This can lead to the generation of "ghost" vehicles through forged messages [56].…”
Section: ) Spoofingmentioning
confidence: 99%